Microbial transmission - Baquero, F. (Fernando); Bouza, Emilio; Gutiérrez Fuentes, José Antonio; Coque, Teresa M. (ASM Press, 2019)
Microbial transmission, the processes by which microbes transit to new environments, is a significant and broad-reaching concept with applications throughout the biological sciences. This collection of reviews, edited by an international team of experts studying and working across a range of disciplines, explores transmission not just as an idea in disease but as a fundamental biological process that acts in all domains of nature and exerts its force on disparate size scales, from the micro to the macro, and across units of time as divergent as a single bacterial replication cycle and the entire course of evolution. In five sections, this overview --Defines the concept of transmission and covers basic processes of transmission, including causality, control strategies, fitness costs, virulence, and selection--Presents numerous combinations of transmission scenarios across the bacterial, animal, and human interface --Examines transmission as the defining characteristic of infectious disease--Presents methods for experimentally verifying and quantifying transmission episodes--Concludes with important theoretical and modeling approaches. Anyone studying or working in microbial colonization, evolution, pathogenicity, antimicrobial resistance, or public health will benefit from a deeper understanding of Microbial Transmission.